Studi Implementasi Kurikulum Berbasis Kompetensi (Kbk) Dan Model Pembelajaran Melalui Pendekatan Modifikasi Dalam Pendidikan Jasmani Di Sekolah Dasar (SD) - Soepartono, (Pendidikan Dasar, 2004)
Penelitian ini mengkaji kurikulum berbasis kompetensi dan model pembelajaran modifikasi penjas. Pengkajian ini difokuskan pada efektivitas keterlaksanaan kurikulum di sekolah dan mengetahui kelebihan dan kelemahan KBK penjas dan model modifikasi. Hasil penelitian menunjukkan bahwa KBK penjas dan model pembelajaran modifikasi efektif (layak) dilaksanakan di SD. Indikatornya adalah: 95,8% siswa senang belajar, siswa antusias mengikuti pembelajaran penjas 97,6%, 96,3% guru mudah memahami kurikulum dan melakukan pembelajaran, 95,6% siswa menyukai bentuk-bentuk aktivitas permainan, pembelajaran dapat memanfaatkan peralatan dilingkungan 99,7%, dan suasana pembelajaran menggembirakan 96,7%. Gambaran hasil kompetensi yang dicapai dibedakan pada tingkat lower class dan tingkat upper class.The purpose of this research is to study the competence-based curriculum and the learning model of physical education modification. The study focuses on the effectiveness of curricular applicability at schools and aims to find out the advantages and disadvantages of the physical-education CBC and the modification model. The research result shows that physical-education CBC and modification learning model are effective or appropriate to be implemented at elementary schools. This conclusion is indicated by the conditions that 95.8% of students like learning, 97.6 of students show enthusiasm for learning physical education, 96.3% of teachers find it easy to understand the curriculum and easily perform the teaching, 95.6% of students prefer games forms of activities, 99.7% of the learningactivities can make use of the instruments in the surrounding, and 96.7% of the atmosphere of learning process is pleasing. The description of competence results achieved is distinguished into lower-class and upperclass levels.